Altered Mitochondrial Signalling and Metabolism in Cancer - Chattopadhyay, Esita; Roy, Bidyut (Frontiers in Oncology, 2017)
Mitochondria being the central organelle for metabolism and other cell signalling pathways have remained the topic of interest to tumour biologists. In spite of the wide acceptance of Warburg’s hypothesis, role of mitochondrial metabolism in cancer is still unclear. Uncontrolled growth and proliferation, hallmarks of tumour cells, are maintained when the cells adapt to metabolic reprogramming with the help of altered metabolism of mitochondria. This review has focussed on different aspects of mitochondrial metabolism and inter-related signalling pathways which have been found to be modified in cancer.